The appropriate approaches for successful transfer of knowledge in contemporary Muslim civilization - Karim, A.H.M Zehadul; Hj.Bakar, Mohd Isa (International Islamic University Malaysia, 2011)
It is often argued that the most important aspect of knowledge and technology is that it must be disseminated properly among the beneficiaries for whom it is actually created. The scientists and the researchers therefore have suggested a number of approaches through which knowledge and technologies have been diffused to many cultures of the world. Likewise, the knowledge and technology created by the modern world and as they are approved by social norms and religious values, may also be disseminated especially to the present Muslim communities. In this context, it is important to identify the most suitable and appropriate approaches and their proper uses in the contemporary Muslim societies. Our understanding of the production, dissemination and the application of knowledge and technology may be enhanced through an attitudinal change of the people and mobilizing them properly through the socio-religious guidance and values. It also tries to evaluate some successful approaches so far employed in transferring knowledge and technology pertinent to agricultural development throughout the Muslim world. Based on the discussion, the paper concluded in the form of some suggestions which the policy planners in the Muslim countries may adopt in their planning strategies for scientific innovation and transferring knowledge.